Analysis of the Position of Wills as an Effort to Anticipate Disputes over the Distribution of Inheritance Assets - Aziz, Agus Hiftirul (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The death of someone who left a will often creates disputes between heirs because the contents state that they will give their property to one person in excess of the share that the other heirs should receive, giving rise to jealousy and feelings of injustice. In order to provide justice and legal certainty for heirs regarding their shares, the state has regulated this in a legal regulation called inheritance law. Inheritance law explains the maximum limit for giving assets in a will and the portions that each heir will and must receive. This research aims to find out and analyze the position of testamentary deeds in anticipating disputes over the distribution of inheritance and the role of the Inheritance Agency in implementing testamentary deeds and issuing certificates of inheritance rights as an effort to anticipate disputes over the division of inheritance. By using the Sociological Juridical study method, we can find the reality in the field in research. This method seeks data by means of interviews and data found in the field, to then analyze the legal problems that occurred in the case. In the research process carried out, it was found that wills in the distribution of inherited assets have an important position and their implementation always takes priority, although it does not rule out the possibility of problems or disputes for both the recipient of the will and the heirs, then the Inheritance Property Center is the agency that has the role and authority in opening will and make a certificate of inheritance rights for the share received by each heir.